Optimal Design and Experimental Research of the Chain Plate based on FEM - Liu Ying; Fu Zhenming; Liu Rongrong (Jixie chuandong)
By analyzing the chain plate force situation,improving the chain plate structure of the chain plate shape is puts forward,the forces of the weak links of the chain plate is changed and the tensile stress the maximum tensile stress area is reduced. According to the forces of the outer chain plate arc structure,the multi- arc segment curve segment design method is proposed to improve the chain tensile strength and fatigue strength of the chain plate. By the experimental verification,comparing with the traditional chain plate shape,the tensile strength of the this chain plates is increased by 5% 10% and the fatigue performance is increased by 6% 12%.